Effects of flywheel resistance training on the running economy of young male well-trained distance runners - Weng, Yingying; Liu, Haochong; Ruan, Tingting; Yang, Wenpu; Wei, Hongwen; Cui, Yixiong; Ho, Indy Man Kit; Li, Qian (Frontiers in Physiology, 2022)
The study aimed to investigate the effect of flywheel accentuated eccentric loading (AEL) training on the running economy (RE) of young male well-trained distance runners. Twenty-two runners participated and were randomly assigned to the flywheel (FG, n=12) and the control group (CG, n=10). Traditional endurance training was performed in both groups three times a week for 6-week, while traditional resistance and flywheel AEL training was added to the CG and FG respectively. Subjects performed the incremental exercise test, squat jump, and countermovement jump (CMJ) before and after training. The results showed that (1) the RE at 65% of peak oxygen consumption (VO2peak), 75% VO2peak, and 85% VO2peak improved significantly after 6 weeks of training (p<0.01, Effect size (ES)=0.76; p<0.01, ES=1.04; p<0.01, ES=1.85) in FG, and the RE of 85% VO2peak in FG was significantly lower than CG (p<0.05, ES=0.30); (2) in post-training, both squat jump (p<0.01, ES=0.73) and CMJ (p<0.01, ES=1.15) performance, eccentric utilization ratio (p<0.04, ES=0.44), the rate of force development (RFD) of squat jump (p<0.05, ES=0.46), and CMJRFD (p<0.01, ES=0.66) were significantly improved in FG. And there are no significant differents in CG group because it was maintain training for our participants. Our findings showed that (1) flywheel AEL training improves the muscles' explosive strength and other neuromuscular functions, and improves the athlete’s running economy under 65%, 75%, and 85% VO2peak, which potentially increases endurance performance. (2) Flywheel AEL training can improve the height, RFD, and the eccentric utilization ratio of squat jump and CMJ, and other lower limb elastic potential energy indicators of the young male, well-trained distance runners.